1997
DOI: 10.1212/wnl.49.6.1564
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal stimulation for Parkinson's disease

Abstract: There has been renewed interest in functional surgery as treatment for Parkinson's disease (PD). Although pallidotomy and chronic pallidal stimulation are highly effective in suppressing levodopa-induced dyskinesia (LID), both methods also seem to be effective in reducing parkinsonian disability. However, the simultaneous improvement of LID and motor signs is hard to explain with the classic model of basal ganglia circuitry. Taking advantage of the fact that deep brain stimulation is reversible and that implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
175
3
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 254 publications
(187 citation statements)
references
References 17 publications
8
175
3
1
Order By: Relevance
“…152 Three independent studies observed that monopolar HFS through electrode contacts in the ventral GPi significantly improved rigidity and levodopa-induced dyskinesias, and at times worsened bradykinesia. [153][154][155] On the other hand, stimulation of the proximal contacts putatively within the dorsal GPi led to improvement in bradykinesia and rigidity, but occasionally produced dyskinesias at higher voltages. These studies were unable to quantify the extent of current spread in each patient, making it unclear what cellular substrates were actually modulated for each stimulation paradigm.…”
Section: Targets Within a Target: The Concept Of Motor Subcircuitsmentioning
confidence: 99%
“…152 Three independent studies observed that monopolar HFS through electrode contacts in the ventral GPi significantly improved rigidity and levodopa-induced dyskinesias, and at times worsened bradykinesia. [153][154][155] On the other hand, stimulation of the proximal contacts putatively within the dorsal GPi led to improvement in bradykinesia and rigidity, but occasionally produced dyskinesias at higher voltages. These studies were unable to quantify the extent of current spread in each patient, making it unclear what cellular substrates were actually modulated for each stimulation paradigm.…”
Section: Targets Within a Target: The Concept Of Motor Subcircuitsmentioning
confidence: 99%
“…48 The complexity of the GPi might explain this variability of effect. 49,50 Some studies have reported an improvement in quality of life, largely related to the improvement in dyskinesias.…”
Section: Beneficial Effectmentioning
confidence: 99%
“…In fact, STN stimulation per se cannot ameliorate LID without decreasing dopaminergic medication [36]. Contrary to this, GPi stimulation may itself decrease the severity of LID [37]. The interaction between STN and GPi activity has been suggested to play a major role in the pathogenesis of dyskinesia, and the amelioration of stimulation-related dyskinesia through proximal contact (i.e., stimulating pallido-subthalamic fibers) shown in previous reports and our own young onset PD (YOPD) patients suggests a more beneficial effect of GPi than STN in ameliorating treatment-related dyskinesia.…”
Section: The Effect Of Target On Reducing Medication Dosagesmentioning
confidence: 94%